Effectiveness of non-biodegradable poly(2-hydroxyethyl methacrylate)-based hydrogel particles as a fibroblast growth factor-2 releasing carrier. Issue 11 (November 2015) - Takeda, Kahoru; Kitagawa, Haruaki; Tsuboi, Ririko; Kiba, Wakako; Sasaki, Jun-Ichi; Hayashi, Mikako; Imazato, Satoshi
Highlights: We developed non-biodegradable hydrogel particle as drug carrier for dental resins. The release of BSA or FGF-2 from hydrogel particles could sustain for up to 14 days. The activity of FGF-2 was maintained for over 2 weeks within the particles. The hydrogel is promising for dental resins to provide tissue regenerative function. Abstract: Objectives: Dental resin-based restorative materials are used in a variety of dental treatment modalities such as root-end filling, perforation sealing, and adhesion of fractured roots. However, the prognosis after such treatments is not necessarily favorable because they fail to promote healing of the surrounding alveolar tissue. In the present study, non-biodegradable poly-2-hydroxyethyl methacrylate (polyHEMA)-based hydrogel particles were fabricated as a carrier vehicle for drug delivery that is applied to dental resins. Methods: The loading and release characteristics of bovine serum albumin (BSA) and fibroblast growth factor-2 (FGF-2) from the polyHEMA-based hydrogel particles were evaluated over time in culture. The hydrogel particles were immersed into an aqueous FITC-labeled BSA solution and were observed using confocal laser scanning microscopy (CLSM). To determine the activity of the FGF-2 released from the particles, the proliferation of osteoblast-like cells cultured with eluates collected from the particles for up to 14 days was determined. Results: CLSM revealed that BSA was adsorbed to the surface of the hydrogel particles. A sustained release of BSA and FGF-2 from the particles was detected for up to 14 days. The eluates from the FGF-2-loaded particles increased the proliferation of the osteoblast-like cells, suggesting that the activity of FGF-2 was maintained for at least 2 weeks within the particles. Significance: These polyHEMA-based non-degradable hydrogel particles may be useful tools that can be applied to dental restorative materials to achieve sustained delivery of drugs that promote tissue regeneration.